-x+2y+z=-3

x-4y+2z=-7

-3x+2y-2z=4

### 1 Answer | Add Yours

`-x+2y+z=-3 ----(1)`

`x-4y+2z=-7 ---(2)`

`-3x+2y-2z= 4 -----(3)`

`(2)+(3)`

`x-4y+2z-3x+2y-2z = -7+4`

`-2x-2y = -3 ----(4)`

`(1)xx2-(2)`

`2(-x+2y+z)-(x-4y+2z) = 2xx(-3)+7`

`-3x+8y = 1 ----(5)`

`(4)xx4+(5)`

`-11x = -11`

`x = 1`

From (4) we get` y = 1/2`

From (1) we get `z = -3.`

*So the answers are x = 1,y = 1/2 and z = -3*

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes